Barriers and facilitators of childhood COVID-19 vaccination among parents: A systematic review - Yusra Habib Khan; Maria Rasheed; Tauqeer Hussain Mallhi; Muhammad Salman; Abdulaziz Ibrahim Alzarea; Abdullah Salah Alanazi; Nasser Hadal Alotaibi; Salah-; Ahmed D. Alatawi; Muhammad Hammad Butt; Sami I. Alzarea; Khalid Saad Alharbi; et al. (Frontiers Media S.A., 2022)
BackgroundThe acceptance of vaccination against COVID-19 among parents of young children plays a significant role in controlling the current pandemic. A wide range of factors that influence vaccine hesitancy in adults has been reported worldwide, but less attention has been given to COVID-19 vaccination among children. Vaccine hesitancy is considered a major challenge in achieving herd immunity, and it is more challenging among parents as they remain deeply concerned about their child's health. In this context, a systematic review of the current literature is inevitable to assess vaccine hesitancy among parents of young children to ensure a successful ongoing vaccination program.MethodA systematic search of peer-reviewed English literature indexed in Google Scholar, PubMed, Embase, and Web of science was performed using developed keywords between 1 January 2020 and August 2022. This systematic review included only those studies that focused on parental concerns about COVID-19 vaccines in children up to 12 years without a diagnosis of COVID-19. Following PRISMA guidelines, a total of 108 studies were included. The quality appraisal of the study was performed by Newcastle-Ottawa Scale (NOS).ResultsThe results of 108 studies depict that vaccine hesitancy rates differed globally with a considerably large number of factors associated with it. The highest vaccine hesitancy rates among parents were reported in a study from the USA (86.1%) and two studies from Saudi Arabia (>85%) and Turkey (89.6%). Conversely, the lowest vaccine hesitancy rates ranging from 0.69 and 2% were found in two studies from South Africa and Switzerland, respectively. The largest study (n = 227,740) was conducted in Switzerland while the smallest sample size (n = 12) was represented by a study conducted in the USA. The most commonly reported barriers to childhood vaccination were mothers' lower education level (N = 46/108, 43%), followed by financial instability (N = 19/108, 18%), low confidence in new vaccines (N = 13/108, 12%), and unmonitored social media platforms (N = 5/108, 4.6%). These factors were significantly associated with vaccine refusal among parents. However, the potential facilitators for vaccine uptake among respondents who intended to have their children vaccinated include higher education level (N = 12/108, 11%), followed by information obtained through healthcare professionals (N = 9/108, 8.3%) and strong confidence in preventive measures taken by the government (N = 5/81, 4.6%).ConclusionThis review underscores that parents around the globe are hesitant to vaccinate their kids against COVID-19. The spectrum of factors associated with vaccine hesitancy and uptake varies across the globe. There is a dire need to address vaccine hesitancy concerns regarding the efficacy and safety of approved vaccines. Local context is inevitable to take into account while developing programs to reduce vaccine hesitancy. There is a dire need to devise strategies to address vaccine hesitancy among parents through the identification of attributing factors.